Volunteering of people with disability - null, null; Marková, Aneta (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2020)
This article deals with the volunteering of people with disability. Currently, this issue is becoming of interest to both the expert and nonexpert population. The introduction focuses on the clarification of the research and points out the studies that deal with this issue. The crucial part of this article is in the results of the research that was carried out as the author’s dissertation. The goal was to clarify what factors affect the participation of people with disability in volunteering from the point of view of volunteers with disability. We chose the method of Strauss and Corbin’s Grounded Theory. We used it to analyze 25 interviews with volunteers with disability. The interview analysis showed that five main factors affected the participation of people of disability in volunteering. The first factor included the advantages of volunteering for volunteers, the second were barriers from volunteers, organizations, the third included the presence or absence of a social role, the fourth was social unfulfilment and the fifth was activation. The final phase of the analysis showed that the main issue for volunteers with disability was the lack of social fulfilment (which is based on the presence or absence of a specific social role), which is significant for a volunteer with disability. Specific roles include the role of a parent, an employee, a partner or a fullyfunctioning member of the society. The results in the concluding discussion are compared with Wolfensberger’s Social Role Valorization Theory.
Keywords: Disability; volunteering; volunteer; Grounded Theory